TCP/IP illustrated : the protocols - Fall, Kevin R.; Stevens, W. Richard (Upper Saddle River, NJ : Addison-Wesley, 2012)
The book is a detailed and visual guide to today's TCP/IP protocol suite. It demonstrates each protocol in action through realistic examples from modern Linux, Windows, and Mac OS environments.
Stevens' name appears first on the earlier edition.
v. 1. The protocols
Includes bibliographical references and index.
rua 29/10/13
Loans
Keywords: TCP/IP (Computer network protocol); TCP/IP - illustrated